(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2005)
A limestone sample from southern Bosnia and Herzegovina near Fojnica town yielded extremely abundant and well-preserved radiolarians. The radiolarians are late Ladinian in age and clearly indicate the Spongoserrula fluegeli Subzone of Muelleritortis cochleata Zone based on the index forms and associated fauna. A highly diverse spumellarian fauna is described from this sample. Within the defined spumellarian fauna, five genera (Ligulatubus, Tubospongopallium, Hexacatoma, Octostella and Discofulmen) seventeen species (Dumitricasphaera galeata, D. trialata, Spongostylus bosniensis, Spongopallium crassum, Ligulatubus yaoi, Tubospongopallium gracile, T. kozuri, T. tornatum, Archaeospongoprunum globosum, Veghicyclia cruciforma, V. krystyni, Hexacatoma elegantissima, H. nobleae, Octostella pulchra, Pentaspongodiscus similediscus, Discofulmen dumitricai, D. ishidai) are new.